The Effect of Music Therapy on Improving Sleep Quality in Children During Hospitalization: Literature Review - Dwining Handayani; Siti Karimatul Kamila; R.A. Helda Puspitasari; Ayu Dewi Nastiti; Erik Kusuma (Global Health Science Group, 2023)
Hospitalization is a crisis situation that occurs in children when they are treated at the hospital, one of the conditions experienced by children when they are sick is the reduced need for sleep. The quality of sleep in children is very necessary when sick to boost the immune system in a child's body so that it will help in the healing process of an illness that is experienced. To explore and look for the effect of music therapy on improving the quality of sleep in children during hospitalization. This study used the literature review method with article searches conducted on the Pubmed, Science Direct and Google Scholar electronic databases. There were 1,891 articles on PubMed, Science Direct and Google Scholar, but only 10 articles met all inclusion criteria and were reviewed. There is an effect of music therapy on improving sleep quality in children during hospitalization. it can be concluded that one of the non-pharmacological therapy programs in improving the quality of sleep in children while being treated at the hospital is using music therapy. This is evidenced by the results of several studies, namely the average quality of sleep in children who underwent hospitalization in the group before and after the administration of music therapy experienced an increase in the quality of children's sleep. Giving music therapy can be given through a tape recorder, MP3 which is usually given at a certain time. Music is received by the hearing organs which are then channeled to the center of the brain called the limbic system which regulates emotions in humans.